2019
DOI: 10.21608/jpp.2019.62861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intercropping of some Legume Forage Crops with Maize Under Levels of Mineral Npk and Nano Npk Fertilizer

Abstract: A field experiment was carried out at Mallawi Agricultural Research Station, Minia Governorate, ARC, during two successive summer seasons of 2017 and 2018 to study the effect of intercropping three fodder crops on productivity, quality and profitability of maize cv. Giza 168 and using different rates of NKP nano + mineral fertilizer. A complete Randomized Block Design in a split plot arrangement with four replicates was used in both seasons. Main plots were devoted for the following three fodder crops guar, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the combination of foliar application with RDF resulted in a significant increase in grain and straw yield, as well as improvements in quality parameters. Similar findings have been reported in studies conducted by Yomso and Menon (2021), Mundhe et al (2022), Ahmed et al (2019), Sannathimmappa et al (2023), Iqbal (2019), and Midde et al (2022).…”
Section: Yield Attributessupporting
confidence: 88%
“…Furthermore, the combination of foliar application with RDF resulted in a significant increase in grain and straw yield, as well as improvements in quality parameters. Similar findings have been reported in studies conducted by Yomso and Menon (2021), Mundhe et al (2022), Ahmed et al (2019), Sannathimmappa et al (2023), Iqbal (2019), and Midde et al (2022).…”
Section: Yield Attributessupporting
confidence: 88%
“…The cultivation area was determined, and soil samples were taken from different places before planting at a depth of (0-30 cm). They were mixed and blended well, then ground and sifted through a sieve with a diameter of 2 mm to analyze some of their chemical and physical characteristics, which are shown in Table (1). A factorial experiment was carried out according to the randomized complete block design (R.C.B.D).…”
Section: Methodsmentioning
confidence: 99%
“…Soil degradation due to a lack of organic matter and lack of nutrients and following the wrong agricultural methods such as the use of fertilizers and non-rational pesticides and irrigation by traditional methods, which cause the depletion of nutrients from the soil and not replace them and increase the content of lime and the high rate of pH leads to a reduction in production and a lack of availability of nutrients. [1], which called for the need to compensate for the deficiency through the fertilization process, as the researchers confirmed that foliar feeding is optimal to compensate for the deficiency that occurred, although it is often supplementary feeding, it is characterized by its ability to quickly treat nutrient deficiency, especially when there are problems in supplying nutrients through the roots. Plant and can contribute to compensation for a certain amount of land addition when properly managed [2].…”
Section: Introductionmentioning
confidence: 99%